2000
DOI: 10.1161/01.hyp.35.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Electrocardiographic Left Ventricular Hypertrophy in Hypertensive Patients

Abstract: Abstract-Obesity 3,4 has been associated with increased morbidity and mortality. However, low sensitivity of standard voltage criteria for detection of LV hypertrophy (LVH) has limited utility of the ECG for identification of patients with LVH. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Although Cornell voltage criteria modestly improve ECG detection of LVH in hypertensive patients, 6,7 the product of Cornell voltage and QRS duration (Cornell voltage-duration product), 8,9 an approximation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 34 publications
12
71
1
3
Order By: Relevance
“…In addition, the LIFE investigators also showed that obese patients tended to have lower Sokolow-Lyon voltages than non-obese patients but had higher Cornell product. 20 The importance of detecting LVH in CAD patients is based on several reasons. Firstly, three previous studies in CAD patients have demonstrated that the relative risk of cardiac death conferred by LVH was 2.14, 2.4 and 2.1 after adjustment for other factors including hypertension and the number of coronary vessels affected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the LIFE investigators also showed that obese patients tended to have lower Sokolow-Lyon voltages than non-obese patients but had higher Cornell product. 20 The importance of detecting LVH in CAD patients is based on several reasons. Firstly, three previous studies in CAD patients have demonstrated that the relative risk of cardiac death conferred by LVH was 2.14, 2.4 and 2.1 after adjustment for other factors including hypertension and the number of coronary vessels affected.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and insulin resistance have been implicated in the pathogenesis of non-hypertensive LVH. Obesity has been demonstrated to be an independent predictor of left ventricular chamber size, left ventricular wall thickness and left ventricular mass [31,32]. Insulin has been demonstrated to have trophic effects on cardiomyocytes in cell culture and may act as a growth factor, promoting the development of LVH [33].…”
Section: Discussionmentioning
confidence: 99%
“…ECGs were then assessed centrally, using the Cornell product and Sokolow-Lyon voltage criteria, which had been used in the LIFE (Losartan Intervention for Endpoint Reduction in Hypertension) study and validated [17][18][19][20][21] in a large number of patients. Furthermore, the Cornell product criteria have been shown to be more sensitive in diagnosing LVH in obese patients and were thus considered to be more robust in assessing the presence or absence of LVH in this study [22].…”
Section: Detection Of Lvhmentioning
confidence: 99%